Answer:
-(x + 6)(x - 7)
Step-by-step explanation:
The expression that we have can also be expressed in the following way:
- (x ^ 2 - x - 42)
Now to factorize we must find two numbers that multiplied by -42 and the sum of these numbers by -1.
these numbers are: -7 and 6
-7 * 6 = -42
-7 + 6 = -1
Thus:
- (x + 6) (x - 7)
Answer:
Step-by-step explanation:
use ''sled tutor'' its basically like live tutoring and its for free
Answer:
1: (4,1) x=4 y=1
2: (1,10) x=1 y=10
3: (-25/4,5) x= -25/4 y=5
Step-by-step explanation:
It would be a lot to explain all three so if you really need it just ask
Keep doing each step manually, and see where it slips up:
−7.9+8.2−3.4+2.1=−1
−7.9+8.2+(−3.4)+2.1=−1
−7.9+(−3.4)+8.2+2.1=−1
(−7.9+(−3.4))+(8.2+2.1)=−1
−11.3+10.3=−1
Answer:
No solutions
Step-by-step explanation:
There can be no solutions to your question